ANALISIS BIBLIOMETRIK PADA SCOPUS DENGAN KEYWORD “STREAMING VIDEO ON DEMAND” MENGGUNAKAN VOSVIEWER - Yunisa Sofianti; Fajar Ramadhan (Politeknik Bisnis Indonesia, 2023)
There have been many researchers who have conducted research trends on streaming video on demand. Based on this, over the past few years, there has been a growing popularity and interest in streaming video on demand. This is evident through the increasing number of video on demand streaming companies entering various countries and being matched by the increasing users of these services. Through this, it provides an opportunity to advance the film industry, both nationally and internationally. This research uses bibliometric analysis with quantitative descriptive method. Bibliometric analysis is carried out by collecting literature results in the form of scientific papers obtained from Scopus with the keyword